2012
DOI: 10.1167/iovs.11-8068
|View full text |Cite
|
Sign up to set email alerts
|

Replication Analysis for Severe Diabetic Retinopathy

Abstract: This study nominates several novel genetic loci that may be associated with severe diabetic retinopathy. In order to confirm these findings, replication and extension in additional cohorts will be necessary as susceptibility alleles for diabetic retinopathy appear to be of modest effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
0
42
1
Order By: Relevance
“…The third study conducted in 973 cases (subjects with PDR and diabetic macular edema) versus 1856 controls (all others including NPDR) of Caucasian type 1 diabetics found borderline significance at several SNPs/loci with DR in a combined meta-analysis 27 (Table 4). However, a replication analysis conducted on the top signals in the WESDR type 1 diabetic did not confirm these associations 97 . The most recent DR GWAS study, conducted by the authors and colleagues, compared 1007 Chinese type 2 diabetic subjects with “extreme DR phenotype”, defined as 570 individuals with diabetes ≥ 8 years duration without DR (controls) versus 437 individuals with PDR (cases) (Table 4).…”
Section: Genetic Factors For Drmentioning
confidence: 91%
“…The third study conducted in 973 cases (subjects with PDR and diabetic macular edema) versus 1856 controls (all others including NPDR) of Caucasian type 1 diabetics found borderline significance at several SNPs/loci with DR in a combined meta-analysis 27 (Table 4). However, a replication analysis conducted on the top signals in the WESDR type 1 diabetic did not confirm these associations 97 . The most recent DR GWAS study, conducted by the authors and colleagues, compared 1007 Chinese type 2 diabetic subjects with “extreme DR phenotype”, defined as 570 individuals with diabetes ≥ 8 years duration without DR (controls) versus 437 individuals with PDR (cases) (Table 4).…”
Section: Genetic Factors For Drmentioning
confidence: 91%
“…Interestingly, AKT3 is a serine/threonine kinase regulating cell survival, insulin signaling and angiogenesis, and has been shown to be activated by platelet-derived growth factor and insulin-like growth factor 1, which have both been implicated in PDR [87]. This association was not replicated in a cohort of type 1 diabetic patients from the Wisconsin Epidemiologic Study of Diabetic Retinopathy but new genetic loci potentially associated with severe DR were identified [88]. The strongest association was at rs4865047, an intronic SNP in the gene CEP125 .…”
Section: Methods Of Literature Reviewmentioning
confidence: 99%
“…Another genome-wide meta-analysis using Genetics of Kidney in Diabetes (GoKinD) and Epidemiology of Diabetes Intervention and Control Trial (EDIC) samples identified several SNPs at close to a genome-wide level for severe diabetic retinopathy (rs476141, p=1.2×10 ; rs10521145, p=3.4×10 −6 ) [17]. A replication analysis for severe diabetic retinopathy was conducted in a cohort of diabetic individuals from the Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR) [18].…”
Section: Introductionmentioning
confidence: 99%